The molecular mechanism of the protective effect of tianeptine against ovarian ischemia-reperfusion injury - Betul Kalkan; Bulent Yavuzer; Aydin Aliyev; Osman Kagan Cakir; Fusun Gozen; Ali Sefa Mendil; Taha Abdulkadir Coban; Halis Suleyman (Scientific Reports)
Abstract Torsion of the ovary is a gynecologic emergency that occurs when the ovary and fallopian tube rotate around the infundibulopelvic ligament, causing ischemic changes in the adnexa. Tianeptine is an atypical antidepressant that has been shown to be effective in treatment-resistant depression and has fewer side effects than other antidepressants. In this study, the protective effect of tianeptine on ovarian ischemia-reperfusion (I/R) injury in female rats was evaluated. Four groups were created from twenty-four female albino Wistar rats before surgery (n = 6/each group): TPG (5 mg/kg/orally tianeptine-only), SG (sham operation), OIR (ovarian I/R), and TOIR (5 mg/kg/orally tianeptine + I/R). One hour before surgery procedures, the TPG and TOIR applied tianeptine. Tianeptine administration procedure was repeated once daily for six days. Under 60 mg/kg intraperitoneal (IP) ketamine and sevoflurane (inhaler) anesthesia, the right ovaries, fallopian tubes, and vessels in the OIR and TOIR groups were clamped by torsion. After 3 h of ischemia, a 6-day reperfusion period was started. Tianeptine administration procedure was repeated once daily for six days. In the SG group, the abdominal cavity was opened and closed with sutures without any intervention on the ovaries. On the seventh day, rats were sacrificed (120 mg/kg ketamine, IP), and ovaries were extracted. Levels of oxidants (malondialdehyde), antioxidants (total glutathione, superoxide dismutase, and catalase), and pro-inflammatory cytokines (tumor necrosis factor-alpha, interleukin-1β, interleukin-6) were measured in excised ovarian tissue. Ovarian tissues also examined histopathologically and immunohistochemically. I/R increased the levels of oxidants and pro-inflammatory cytokines and decreased the levels of antioxidants in rat ovaries. In parallel, histopathologic and immunohistochemical examination of the ovarian tissue revealed the presence of severe (grade 3) oxidative damage. Tianeptine significantly suppressed oxidative stress and pro-inflammatory cytokine increases related with I/R in the ovarian tissue, while also alleviating histopathological damage and oxidative DNA damage. Our experimental results suggest that tianeptine treatment may be effective against I/R-induced ovarian injury.